Parameter Non Spesifk dan Pengujian Toksisitas Ekstrak Etanol Daun Kokang (Lepisanthes amoena) Terhadap Larva Udang Artemia salina leach : Non-Specific Parameters and Toxicity Testing of Ethanol Extract of Kokang Leaf (Lepisanthes amoena) Against Shrimp Larvae Artemia salina leach - Syarifah Irhamnah; Novita Eka Kartab Putri; Hadi Kuncoro (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
The kokang leaves Lepisanthes amoena (Hassk.) Leenh) is a family of Sapindaceae which has been widely used as a traditional medicine, even now there are many formulas for the preparation of kokang leaves. The purpose of this study was to determine non-specific parameters, profile of TLC and to determine the acute toxicity of ethanol extract of kokang leaves against shrimp larvae of Artemia salina leach. The ethanol extract of kokang leaves was obtained by meseration method using 70% ethanol with a yield of 20.97%. The determination of non-specific parameters includes specific gravity, drying losses, total ash content, acid insoluble ash content. The ethanol extract of kokang leaves was analyzed by TLC profile using chloroform: acetone (8: 2) as eluent. Toxicity testing using the BSLT method and data were analyzed using Reed-Muench analysis. The results of the research to determine the non-specific parameters obtained are the average density 0.81 g; shrinkage in drying an average of 1.73%; total ash content on average 18.76%; acid insoluble ash content averaged 2.31%. The results of the TLC profile analysis were observations at UV 254 nm with an Rf value of 0.8. The results of observations on UV 366 nm showed two stains with Rf values of 0.7 and 0.8. The results of the acute toxicity test showed an LC?? value of 154.170 ppm. The conclusion based on the research results obtained non-specific parameters of kokang leaves. Based on the results of the TLC profile analysis of the compounds contained in the ethanol extract of kokang leaves, it tends to be non-polar. The LC?? value obtained shows that the ethanol extract of kokang leaves is toxic with a value of 154.170 ppm